Lack of evidence of isoniazid efficacy for the treatment of MDR/XDR-TB in the presence of the katG 315T mutation. Issue 4 (12th October 2017) - Chesov, Dumitru; Ciobanu, Nelly; Lange, Christoph; Schön, Thomas; Heyckendorf, Jan; Crudu, Valeriu
We are grateful for the response by E. Heldal to our correspondence. Similar to other reports [1] from the World Health Organization (WHO) Euro-Region we found that a high proportion (88%) of Mycobacterium tuberculosis strains from patients with multidrug-resistant (MDR)/extensively drug-resistant (XDR) tuberculosis (TB) in the Republic of Moldova had a katG 315T mutation, which is strongly suggestive that high-dose isoniazid should not be part of a standardised treatment regimen for patients with MDR/XDR-TB in this country. Further studies are needed to address the possible benefits of high-dose isoniazid therapy adequately http://ow.ly/XDcd30fiFeR